Conductive materials in anaerobic digestion: From mechanism to application - Wu, Yu; Wang, Shu; Liang, Danhui; Li, Nan (Bioresource technology, 2020)
[Display omitted] •Summarize the current understanding of the CMs enhancement on methanogenesis.•Biochar, AC and carbon cloth thermodynamically enhance methanogenesis.•MWCNT, biochar, and carbon cloth kinetically enhance methanogenesis significantly.•Adding CMs trigger DIET for efficient syntrophic metabolism.•CM supplemented can increase electron capture capability and accelerate reaction rate. Anaerobic digestion (AD) is an effective strategy combined advantages of maintaining the global carbon flux and efficient energy conversion. Various conductive materials (CMs) have been applied in anaerobic digesters to improve the performance of anaerobic fermentation and methanogenesis, including carbon-based CMs and metal-based CMs. Generally, CMs facilitated the AD thermodynamically and kinetically because they triggered more efficient syntrophic metabolism to increase electron capture capability and accelerate reaction rate as well as enhance the performance of AD stages (hydrolysis-acidification, methanogenesis). Besides, adding CMs into anaerobic digester is benefit to dealing with the deteriorating AD, which induced from temperature variation, acidified working condition, higher H2 partial pressure, etc. However, few CMs exhibited inhibition on AD, including ferrihydrite, magnesium oxide, silver nanoparticles and carbon black. Inhibition comes from a series of complex factors, such as substrate competition, direct inhibition from Fe(III), Fe(III) reduction of methanogens, toxic effects to microorganisms and mass transfer limitation.